2015
DOI: 10.1038/nprot.2015.031
|View full text |Cite|
|
Sign up to set email alerts
|

RNAi-based biosynthetic pathway screens to identify in vivo functions of non-nucleic acid–based metabolites such as lipids

Abstract: The field of metabolomics continues to catalog new compounds, but their functional analysis remains technically challenging, and roles beyond metabolism are largely unknown. Unbiased genetic/RNAi screens are powerful tools to identify the in vivo functions of protein-encoding genes, but not of non-proteinaceous compounds such as lipids. They can, however, identify the biosynthetic enzymes – of these compounds- findings that are usually dismissed, as these typically synthesize multiple products. Here, we provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…SLs are highly conserved components of cell membranes having regulatory roles in growth control and aging in a wide range of organisms ( Cutler et al., 2014 ). SL works as an intermediate for the production of ceramide (Cer), a key product for the synthesis of glucosylceramide and sphingomyelin (SM) ( Zhang et al., 2015 ) ( Figure 4 A). Cer is produced from SM in UV- and IR-treated mammalian cells ( Zeidan et al., 2008 ), whereas an increased synthesis of SM from Cer is associated to accelerated development and aging ( Cutler et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLs are highly conserved components of cell membranes having regulatory roles in growth control and aging in a wide range of organisms ( Cutler et al., 2014 ). SL works as an intermediate for the production of ceramide (Cer), a key product for the synthesis of glucosylceramide and sphingomyelin (SM) ( Zhang et al., 2015 ) ( Figure 4 A). Cer is produced from SM in UV- and IR-treated mammalian cells ( Zeidan et al., 2008 ), whereas an increased synthesis of SM from Cer is associated to accelerated development and aging ( Cutler et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphatidic acid is dephosphorylated to yield DAG, which is converted into phosphatidylcholine (PC) and phosphatidylethanolamine (PE), which can be both intermediates for the formation of phosphatidylserine (PS). PS and phosphatidylinositol (PI) are generally synthesized from cytidine diphosphatediacylglycerol (CDP-DAG), substrate for the synthesis of phosphatidylglycerol (PG) and cardiolipin ( Zhang et al., 2015 ). Quantitative glycerophospholipids MS profiling, upon starvation and UV treatment, showed a change of the DAG downstream products, indicating a preferential direction in the phospholipid synthesis ( Figures 4 D and S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The worm samples were thawed and homogenated firstly by a sonicator (Fisher Scientific, Model 505 sonic dismembrator, Fair Lawn, NJ, USA), and then freeze-dried (FreeZone 4.5 Freeze Dryer, Labconco, Kansas City, MO, USA) for 24 hrs. The extraction of SLs from C. elegans was carried out according to a modified Bligh and Dyer's method 37, 38. Briefly, 30 mg of worms were added with 2 ml of methanol (MeOH) and 1 ml of chloroform (CHCl 3 ), vortexed for 1 min, and incubated in a water bath (TW12, Julabo, Allentown, PA) at 48°C for 24 hrs.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate possible roles of Kelch repeat-containing proteins in modulating intestinal morphogenesis, we carried out RNAi knockdown of 11 C. elegans proteins containing Kelch repeats (based on the SMART database) using worms expressing the lumenal membrane marker ACT-5::GFP. We identified that the previously uncharacterized gene C53A5.6 shows fully penetrant L1 larval lethality with severe intestinal morphogenesis defects upon standard RNAi treatment [ 31 ] ( Figure 1 and Table S1). The protein encoded by C53A5.6 is distinct from other Kelch repeat proteins owing to the presence of an N-terminal RING domain; therefore, we named this gene rike-1 ( RI NG- and Ke lch-containing protein).…”
Section: Resultsmentioning
confidence: 99%